Analysis of methodological components and available resources in Costa Rica to generate food composition data - Hidalgo Víquez, Cindy María (2021)
Objective Analyze the methodological components and available resources for generation of food composition data (FCD) in Costa Rica (CR). Methods Laboratories that perform food composition analysis in CR were consulted in order to characterize them and evaluate which complied with the standards established by international authorities for the generation of FCD. Finally, the applicability of the technical criteria determined by the international authorities for food and nutrient analysis was evaluated with experts in CR. Results We found that several entities have the capacity of both in infrastructure and human resources to generate FCD, however their work is disjointed, they have a very limited budget and there is no national FCD system. One of the limitations that we identified is that public laboratories don’t offer analysis of water-soluble vitamins, which limits obtaining complete data on food samples. In addition, there is no consensus in the country regarding which foods and nutrients should be included in the food composition databases (FCDB). Costa Rica need to improve the generation of our own data in the country for some specific foods. Conclusions Promote alliances between entities that have the capacity to produce data and work towards achieving an integrated FCD system in the country.